COMMUNITY HEALTH TOURISM PROMOTION STRATEGY CHARACTERIZING CYCLING FROM A TOURISM COMMUNICATION PERSPECTIVE (International Journal of Cultural and Social Science, 2026)
This study analyzes the community-based health tourism promotion strategy implemented by the Mencirim Gowes Community in Sei Mencirim Village, Deli Serdang Regency, North Sumatra, from the perspective of tourism communication. The study is motivated by the underdeveloped potential of local health tourism, although the cycling trend has considerable potential to promote healthy lifestyles, active recreation, social interaction, and sustainable tourism destinations. This research employed a descriptive qualitative approach, with data collected through observation, semi-structured interviews, and documentation involving the leader and members of the Mencirim Gowes Community. The data were analyzed descriptively using source triangulation. The findings show that the community’s promotional strategy is implemented through the 4P marketing mix framework. In terms of product, cycling activities are positioned as a health tourism product that integrates sport, recreation, physical fitness, mental well-being, and social togetherness. In terms of price, the community applies a low-cost model, making the activity accessible to various social groups. In terms of place, cycling routes utilize local tourism potential, rice fields, open natural areas, and destinations such as Wak Jowo Natural Spring. In terms of promotion, the community uses social media, digital storytelling, WhatsApp groups, and collaboration with other cycling communities. The novelty of this study lies in the development of community-based cycling health tourism as a tourism communication strategy that not only promotes destinations but also positions community activities as healthy, inclusive, and sustainable tourism products. This study confirms that community-based health tourism promotion can serve as an alternative model for local tourism development by integrating health, recreation, social solidarity, and the preservation of local potential.